2020
DOI: 10.1177/1742715020917817
|View full text |Cite
|
Sign up to set email alerts
|

The negotiation of sharing leadership in the context of professional hierarchy: Interactions on interprofessional teams

Abstract: While there is growing recognition of leadership as a collective phenomenon, the question of how leadership is shared in the context of hierarchical asymmetry has been neglected in the collective leadership literature. Our article addresses this gap by examining how sharing leadership is negotiated in team interactions that are steeped in asymmetry deriving from the professional hierarchy. Adopting a leadership-in-interaction approach, we draw on fine-grained analysis of observed interactions on interprofessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 70 publications
(141 reference statements)
1
23
0
Order By: Relevance
“…In the critical leadership field, there is interest in phenomena adjacent to managerial shared leadership, as well as relevant analysis tools (e.g. Alvehus, 2019; Empson, 2020; Fox and Comeau-Vallée, 2020; Crevani et al, 2010). This may result in increased interest in studying managerial shared leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the critical leadership field, there is interest in phenomena adjacent to managerial shared leadership, as well as relevant analysis tools (e.g. Alvehus, 2019; Empson, 2020; Fox and Comeau-Vallée, 2020; Crevani et al, 2010). This may result in increased interest in studying managerial shared leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, such managerial constellations may also be looked at as teams, and we note a prominent focus on other types of team within the shared leadership literature (e.g. Carson et al, 2007; Ensley et al, 2006; D'Innocenzo et al, 2016; Fox and Comeau-Vallée, 2020; Wang et al, 2014). Accordingly, we chose the term shared to conceptualise the focal point of this review, drawing on Pearce and Conger’s (2003) widespread definition of shared leadership: ‘…a dynamic, interactive influence process among individuals in groups for which the objective is to lead one another to the achievement of group or organizational goals or both’ (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Studying what the leader does while the collective is directing the action may seem counterintuitive, but it may be crucial for understanding how shared leadership emerges, is maintained, and disappears. Taking an interest in everything the leader may have done before and during the shared leadership process in order to allow or impede it would extend the work of Fox and Comeau-Vallée (2020), in which they partially addressed the conditions that facilitate or hinder the emergence of this form of leadership.…”
Section: Future Researchmentioning
confidence: 99%
“…Such an attempt could contribute to improved collaboration. For example, researchers have recently suggested that collaborative leadership can be supported if clinicians at different hierarchical positions consciously work to foster shared decision making amongst the team and that this work begins long before the decision making stage (Fox & Comeau-Vallée, 2020).…”
Section: Hierarchy In Collaborationmentioning
confidence: 99%